The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00246-015-1277-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function After the Immediate Transitional Period in Very Preterm Infants Using Speckle Tracking Analysis

Abstract: Speckle tracking echocardiography analysis is a feasible and reliable technique that can simultaneously obtain systolic and diastolic volumes, longitudinal deformation and myocardial velocities from one ultrasound window. Preterm hearts maintain cardiac function well during the first weeks of life, even with increased preload as a consequence of a PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
1
35
1
3
Order By: Relevance
“…Nasu et al performed eight serial echocardiograms over the first 72 hours of age and demonstrated no change in LV strain. 8 Czernik et al 14 and de Waal et al 12 each serially observed stable 2DSTE-derived LV GLS in preterm infants from birth to 28 days of age. Hirose et al demonstrated that clinically healthy preterm infants (delivered at < 30 weeks gestation) also have constant 2DSTE-derived LV strain measures from 28 days of age to near term equivalent age (3 months CA).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Nasu et al performed eight serial echocardiograms over the first 72 hours of age and demonstrated no change in LV strain. 8 Czernik et al 14 and de Waal et al 12 each serially observed stable 2DSTE-derived LV GLS in preterm infants from birth to 28 days of age. Hirose et al demonstrated that clinically healthy preterm infants (delivered at < 30 weeks gestation) also have constant 2DSTE-derived LV strain measures from 28 days of age to near term equivalent age (3 months CA).…”
Section: Discussionmentioning
confidence: 96%
“…de Waal et al also found higher LV GLS and SRs in infants with a PDA. 12 It is well documented that a hsPDA significantly increases LV preload, and leads to an increase in LV output. 48 The increase in preload is accompanied by an increase in S but not SRs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is an expanding body of literature on strain and SR in term and preterm infants using both cDTI and STE techniques [8,31,44,49,[56][57][58] . Current research is evaluating the ability of ε and SR to characterize the physiological and pathological changes in diseases such hypoxic ischaemic encephalopathy, pulmonary hypertension, li- gation of a patent ductus arteriosus, and chronic lung disease.…”
Section: Deformation Imagingmentioning
confidence: 99%